1977
DOI: 10.1007/bf00585195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aldosterone on lipid metabolism and renal oxygen consumption in the rat

Abstract: The plasma level of free fatty acids (FFA) in adrenalectomized rats increases by 50% after treatment with aldosterone (2 microng/100 g rat). Lipolytic activity in peripheral fat tissue is lowered after adrenalectomy and doubles after in vivo administration of aldosterone to adrenalectomized rats (measured as free fatty acid release in vitro from epididymal fat tissue). Lypolysis of adipose tissue stimulated by the in vitro presence of ACTH also increases after in vivo administration of aldosterone. Incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is possible therefore that aldosterone itself might be the primary cause of insulin resistance, although currently there is little evidence in the literature for a direct causal link. In animal studies aldosterone treatment has been found to increase plasma NEFA levels, consistent with an effect on AT lipolysis (Kirsten et al 1977), and aldosterone added to human adipocytes in vitro reduces insulin-dependent glucose uptake by 30% (Kraus et al 2005). The relationship between aldosterone and glucose metabolism is poorly understood, but in the light of recent findings linking both primary and secondary aldosteronism with insulin resistance and hyperinsulinaemia, more work to elucidate this metabolic link is warranted.…”
Section: Adipose Tissue Function Following Total Colectomymentioning
confidence: 88%
“…It is possible therefore that aldosterone itself might be the primary cause of insulin resistance, although currently there is little evidence in the literature for a direct causal link. In animal studies aldosterone treatment has been found to increase plasma NEFA levels, consistent with an effect on AT lipolysis (Kirsten et al 1977), and aldosterone added to human adipocytes in vitro reduces insulin-dependent glucose uptake by 30% (Kraus et al 2005). The relationship between aldosterone and glucose metabolism is poorly understood, but in the light of recent findings linking both primary and secondary aldosteronism with insulin resistance and hyperinsulinaemia, more work to elucidate this metabolic link is warranted.…”
Section: Adipose Tissue Function Following Total Colectomymentioning
confidence: 88%
“…It was only associated with the reduction observed in aldosterone levels in study 3, which was not verified in study 4, where dose adjustments were performed to prevent too much body weight loss. Given that aldosterone has rather lipolytic properties 55 , the transient, increased serum FFA may have an inhibitory effect on aldosterone secretion as a part of a compensatory mechanism. Furthermore, even though we see some small changes in FFA with leptin, these are not proportional to the changes in fat mass, suggesting that they may account for some minor but not all of leptin’s effects on body weight/fat mass that are probably due to the decreasing energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…the decreased glucagon-like peptide 1 (GLP-1) concentrations secreted by endocrine L-cells in the distal gut [4,17], 3.) the secondary aldosteronism [20,21]. Furthermore, the finding that RH patients, rather than LAR patients, had a higher serum fasting glucose and higher occurrence of metabolic syndrome when compared with those of control imply that proximal colon may play an important role in glucose control.…”
Section: Discussionmentioning
confidence: 99%